A taste for beauty: On the expected taste, hardness, texture, and temperature of geometric shapes. (September 2022) - Juravle, Georgiana; Olari, Emilia-Liliana; Spence, Charles
Rounded shapes, which have been shown to enhance sweetness, were compared to the perfectly symmetrical Platonic solids. In a first online experiment, participants were presented with a rotating three-dimensional geometric shape (a sphere, the five Platonic solids, and three irregular angular/rounded/naturalistic controls), and indicated their liking for the shape, as well as its perceived hardness, and its expected temperature. The sphere was liked best, followed by the Platonic solids. The sphere was also evaluated as softest, and received the warmest temperature ratings. By contrast, the Platonic solids were rated as harder and significantly colder than the sphere. Experiment 2 investigated whether the liked shapes were also evaluated as looking tastier. Ratings of expected tastiness and the appearance of five shapes selected based on high liking scores and fitted with edible and inedible visual textures were recorded. The sphere was rated as looking tastiest, with edible-textured rounded shapes resulting in significantly tastier ratings. Experiment 3 assessed the taste corresponding to each shape. A sweet and umami preference for rounded shapes was documented, with sour and bitter typically matched to angular shapes. Importantly, the Platonic solids were associated with several tastes. These findings are explained in terms of current theories of crossmodal correspondences, while considering how temperature and texture can be used to modulate expected liking.